HYDROGEN CHARGING OF FUEL CLADDING METHODOLOGY - Jakub Krejčí; Jitka Kabátová; Jan Kočí; Zuzana Weishauptová; Věra Vrtílková (Acta Polytechnica CTU Proceedings)
Hydrogen content is a very important parameter for mechanical properties of fuel cladding, especially after LOCA transients. Therefore, it is necessary to take into account the amount of hydrogen absorbed in the fuel cladding during normal operation (before a hypothetical LOCA). The required value of hydrogen content is possible to reach by a long-term pre-oxidation test or a much shorter hydrogen charging experiment. The methodology of hydrogen charging developed in UJP is described in this contribution. Results of experiments aiming to prepare samples with uniform hydrides and samples with a rim-layer and other hydrides are shown.